Entropy-based analysis of rowing technique: Stroke-rate effects and performance implications - Gao, Y.; Wei, X.; Chen, X. (International Journal of Sports Physiology and Performance, 2026)
Purpose: The study aimed to (1) investigate the influence of different stroke rates on movement variability (MV), defined as normal variations in repeated motions, and (2) explore the relationship between MV and rowing performance.